Attitudes of pupils at senanga secondary school in senanga district in western province of Zambia towards their peers with hearing impairments - Lukonga, Kozwana H. (Lusaka: University of Zambia , School of Medicine, 2015)
The study investigated the attitude of hearing pupils to pupils with hearing impairments and sought to understand how the attitudes of the hearing pupils affected the hearing impaired pupils.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Physiotherapy.
Includes bibliographical references.
Keywords: Hearing impaired children--Zambia.; Persons With Hearing Impairments